Rapid Realist Review of School-Based Physical Activity Interventions in 7- to 11-Year-Old Children - Emmanuel Defever; Michelle Jones (MDPI AG, 2021)
Meta-analysis of physical activity interventions in school settings have revealed low efficacy and that there is a need to explore implementation fidelity. The aim of this rapid realist review was to determine, what physical activity interventions in school settings for children aged 7- to 11-years-old works, for whom, and in what circumstances. The realist synthesis was conducted following RAMESES guidelines. Relevant studies were identified following a systematic search process and data from 28 studies was extracted for evidence to form context-mechanism-outcome configurations that were clustered and refined. Using the five-level socioecological model, the program theories were classified into the levels of intrapersonal (child), interpersonal (teachers), institutional (program content, school administration, and school environment), community (home and neighborhood), and policy. The school level led to most context-mechanism-outcome configurations related to school leadership and policy, workforce structure, program characteristics, and school environment. At each level, we identified features of interventions, alongside implementation considerations that might work to promote efficacy and sustainability. The need to recognize the school environment as part of a complex system with multi-level interaction and influences was a key finding. In line with realist philosophy, the researchers encouraged primary research to confirm, refute, and refine the program theories presented.